Dataset of experimental study investigation of airflow and heat transfer in an insulated box equipped with a phase change material - Tanathep Leungtongkum; Onrawee Laguerre; Denis Flick; Alain Denis; Steven Duret; Nattawut Chaomuang (My University, 2022)
This article contains a detailed description of the experimental protocol of air velocity (by particle image velocimetry - PIV) and temperature measurement (by T-type thermocouples) in an insulated box equipped with a Phase Change Material (PCM). The study was conducted in an empty box and a loaded box with extruded polystyrene slabs (XPS) and methylcellulose slabs (test product). The measurement was conducted at the middle plane and lateral plane. This article contains a complete dataset along with the illustrated figures of conducted experiment. They lead to more understanding of phenomena inside a closed cavity with a cold source and can be useful for validating numerical models, e.g., the results computed by computational fluid dynamic.
Keywords: Thermocouple; Phase-change material; Building Energy and Comfort Optimization